Legal Protection for Victims of Domestic Violence: Sociological Analysis and Legal Implications - Ananta, Nida; Mulyana, Aji; Amalia, Mia (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2025)
Abstract Domestic violence (DV) is a serious problem. Domestic violence can occur in various forms, including physical, psychological, sexual, and economic. This study discusses legal protection for victims of domestic violence (DV) in Indonesia, using a sociological analysis approach and its legal implications. Although there is Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT), its implementation and enforcement still encounter various obstacles. This study highlights the factors that influence the effectiveness of legal protection for victims of domestic violence, including sociological aspects that influence public perception of domestic violence, stigma against victims, and the role of law enforcement institutions. Through qualitative analysis methods, this study reveals that legal protection for victims of domestic violence is not optimal due to various obstacles such as lack of understanding of law enforcement officers, minimal social support, and cultural pressures that often prevent victims from reporting cases. The role of family law in handling domestic violence includes prevention, handling, and recovery. Therefore, the government needs to increase awareness and strengthen legal protection for victims of domestic violence, as well as increase education about domestic violence in the community. Keywords: Domestic violence (KDRT), Causal factors, Impact, Legal protection Abstrak Tindak kekerasan dalam rumah tangga (KDRT) merupakan masalah serius. KDRT dapat terjadi dalam berbagai bentuk, termasuk fisik, psikologis, seksual, dan ekonomi. Penelitian ini membahas perlindungan hukum bagi korban kekerasan dalam rumah tangga (KDRT) di Indonesia, dengan pendekatan analisis sosiologis dan implikasi hukumnya. Meskipun telah terdapat Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga (UU PKDRT), implementasi dan penegakannya masih menemui berbagai kendala. Penelitian ini menyoroti faktor-faktor yang memengaruhi efektifitas perlindungan hukum bagi korban KDRT, termasuk aspek sosiologis yang mempengaruhi persepsi masyarakat terhadap KDRT, stigma terhadap korban, dan peran institusi penegak hukum. Melalui metode analisis kualitatif, penelitian ini mengungkapkan bahwa perlindungan hukum terhadap korban KDRT belum optimal karena berbagai hambatan seperti kurangnya pemahaman aparat penegak hukum, minimnya dukungan sosial, serta tekanan budaya yang sering menghambat korban untuk melaporkan kasus. Peran hukum keluarga dalam penanganan KDRT meliputi pencegahan, penanganan, dan pemulihan. Oleh karena itu, pemerintah perlu meningkatkan kesadaran dan memperkuat perlindungan hukum terhadap korban KDRT, serta meningkatkan edukasi tentang tindak kekerasan di dalam rumah tangga di Masyarakat. Kata Kunci: Kekerasan dalam rumah tangga (KDRT), Faktor penyebab, Dampak, Perlindungan hukum